Primary pancreatic lymphoma: Clinical presentation, diagnosis, treatment, and outcome. (2nd July 2020) - Facchinelli, Davide; Sina, Sokol; Boninsegna, Enrico; Borin, Alex; Tisi, Maria C.; Piazza, Francesco; Scapinello, Greta; Maiolo, Elena; Hohaus, Stefan; Zamò, Alberto; Merli, Michele; Stefani, Piero M.; et al.
Abstract: Primary pancreatic lymphoma (PPL) is a rare disease representing 0.1% of malignant lymphomas, which lacks well‐defined diagnostic and therapeutic protocols. Objectives: To describe PPL clinical, diagnostic and histological characteristics, together with therapy and outcome, in a relatively large series of patients. Methods: The study includes 39 PPL patients, aged ≥15 years, observed from January 2005 to December 2018, in 8 Italian Institutions. Results: The main symptoms were abdominal pain (58%) and jaundice (47%). Lactate dehydrogenase serum levels were elevated in 43% of patients. Histological specimens were mostly obtained by percutaneous (41%) or endoscopic (36%) biopsy, with diffuse large B‐cell lymphoma being the most frequent (69%) histological diagnosis. Chemotherapy was administered alone in 65% of patients, with radiotherapy in 17%, or after surgery in 9%. The 2‐year overall survival (OS) was 62%, the 2‐year progression‐free survival (PFS) 44%. Debulking surgery (with or without chemotherapy) was associated with a significant worse OS. Three (9.4%) of 32 high‐grade patients experienced a central nervous system (CNS) relapse. Conclusions: PPL is rare, often high‐grade, with symptoms and localization similar to other pancreatic malignancies. Biopsy should be the preferred diagnostic method. High‐grade PPL should undergo CNS prophylaxis.